A execução provisória por quantia certa contra devedor solvente no Código de Processo Civil Brasileiro - Marques, Camila Salgueiro da Purificação (2014)
The present study aims focuse on the Brazilian procedural law, specifically the institute of the provisional execution in court rulings, authorized by the Code of Civil Procedure in the cases of appeals that are received only in their non-staying effect, with a procedure regulated by the article 475-O of the Code of Civil Procedure. As such, it encompasses the provisional execution with exact amount against a solvent debtor in the Code of Civil Procedure. The present study is justified by the need to carry out court rulings, mainly the ones provided by first instance judges, in order to avoid that the plaintiff, prevailing party of the demand, wait for the trial of the appeal put in motion by the opposing party, to only then perform the execution. The technique of researching indirect documentation was used, and the approach method is the logical deductive. The research approached the following items: the effectiveness of the court rulings, mainly within the ambit of execution, as well as its sentences, its respective chapters and efficacy; the moment of the efficacy of the decisions, approaching the provisional execution title, the provisional execution and the advanced judicial protection, and the execution of the astreintes ; the concept of the provisional execution, the situations that lead to it, and its distinctive criteria in relation to the definitive execution, specifically the bond and the responsibility of the execution creditor; the procedure of the provisional execution; and other questions considered relevant, even if they don t compose the focus of the study, such as the provisional execution against the Public Treasury, the provisional execution of the fees and the procedural costs, and the specific provisional execution. The investigation shows the necessity and the urgency to carry out the court rulings, and the theme should be continuously studied